Employee Branding and Owner Personal Branding as Drivers of Customer Engagement: Evidence from Digital Small and Medium-sized Enterprises - Hadi Suriono; Riy Dewantoro (Al-Qalam Institute, 2026)
The integration of employee branding and owner personal branding to enhance customer engagement among small and medium-sized enterprises (SMEs) utilizing digital platforms is crucial to examine. This study analyzes the partial and simultaneous effects of employee branding and owner personal branding on customer engagement. A descriptive-quantitative survey design was employed. The population comprised 15,178 SME actors across 12 sub-districts; proportionate stratified random sampling using the Slovin formula (e = 10%) yielded 99 respondents. Data were collected via a five-point Likert-scale questionnaire and analyzed using multiple linear regression. Employee branding has a significant positive effect on customer engagement (β₁ = 0.589; t = 6.203; p < 0.001), as does owner personal branding (β₂ = 0.358; t = 3.693; p < 0.001). The integrated model explains 85.0% of the variance in customer engagement (R² = 0.850; F = 274.817; p < 0.001). These findings contribute to the employer branding literature in the SME-digital context and offer practical guidance for SME practitioners in designing integrated branding strategies that combine employee brand commitment with authentic owner communication on social media platforms.